Extracellular matrix components in bronchoalveolar lavage fluid in quartz exposed rats. Issue 11 (November 1991) - Eklund, A; Tornling, G; Blaschke, E; Curstedt, T
Abstract : To investigate the long term effects of quartz, bronchoalveolar lavage (BAL) and analysis of lung silica were performed in rats (n = 20) one, four, and 12 months after exposure to intratracheally instilled crystalline silica. Total and relative concentrations of silica in the lungs were highest one month after exposure. At this time BAL fluid concentrations of total cells, macrophages, and lymphocytes increased five to 10-fold compared with saline instilled controls (n = 19). The number of polymorphonuclear cells (PMNs) increased about 200-fold. The increased number of PMNs persisted during the year. Furthermore, albumin and fibronectin concentrations increased continually during the year, about two to fivefold the values of controls. Hyaluronan, by contrast, increased during the four month period (about eightfold) but decreased after one year to the one month concentration. Phospholipids in BAL fluid, raised already after one month, remained high at one year. The findings suggest progressive damage of the alveolar and interstitial tissues. Moreover, the increases in components of the extracellular matrix capable of building fibrotic networks are in agreement with the microscopical findings of fibrosis. Because only total cells, macrophages, and albumin concentrations correlated weakly with the silica contents of the lung, it is unlikely that the relation between quartz burden and the reaction in the lung is simple.